The genus Leucophenga (Diptera, Drosophilidae), part VI: the argentata species group from the East Asia, with morphological and molecular evidence - Huang, Jia; Chen, Hongwei (Zootaxa, 2016)
Six species of the Leucophenga argentata species group from East Asia are examined (including one known and five new ones): L. argentata (de Meijere, 1914); L. bicuspidata sp. nov.; L. fuscivena sp. nov.; L. longipenis sp. nov.; L. quadricuspidata sp. nov.; L. tricuspidata sp. nov.; the diagnoses for Asian species of the argentata group and a key to these species are provided. A total of 44 DNA sequences of the mitochondrial COI (cytochrome c oxidase subunit I) gene with BOLD process ID and GenBank accession numbers are provided for these species. The intra- and interspecific pairwise p-distances are summarized. The NJ (Neighbor-joining) and the Bayesian analyses are used to conduct a molecular phylogenetic analysis for the above-mentioned species. The molecular data are used as complementary evidence for the identification of the argentata group species with sexually dimorphic abdominal tergites.